The Effect Of BCA, BRI And Bank Mandiri Performance On The Indonesia Composite Index - Umi Latifah; Fazhar Sumantri (Jurnal Ekonomi Pembangunan, 2020)
The Indonesia Composite Index (ICI) serves as a tool to measure and compare stock price movements in the capital market. The purpose of the research is to analyze the impact of the Operational Efficiency, Net Interest Margin, and Non-Performing Loan Ratios on Bank BCA, BRI, and Bank Mandiri as independent variables. Data used in this research was taken from the Financial Services Authority. The result from the F test shows a significant relationship in Operational Efficiency, Net Interest Margin, and Non-Performing Loan on the Bank BCA, BRI, and Mandiri towards the Indonesia Composite Index. Meanwhile, the t-test shows a significant relationship between Non-Performing Loan on the Bank BCA, Net Interest Margin on the Bank BRI, and all variables on the Bank Mandiri to Indonesia Composite Index. Based on Adjusted R Square; Operational Efficiency Ratio, Net Interest Margin, and Non-Performing Loan towards to Indonesia Composite Index is 88% while the rest of it 12% were influenced by other factors